To study the prevalence and types of nutritional anemia in under-five children with severe acute malnutrition - Jangid, Roshan Kumar; Kumar, Arun; -, Anita; Mahapatra, Chinmaya; Yadav, Manoj; Singhal, Sidhant; Laxminarayan, Kartik (Indian Journal of Child Health, 2020)
Background: Anemia is an important comorbidity in under-five children with severe acute malnutrition (SAM). The data on evaluation of SAM are limited. Aim: This study was done for analysis of incidence and types of anemia prevalent in SAM children. Materials and Methods: It was a hospital-based prospective observational study conducted from July 2017 to December 2018. A total of 260 children of age <5 years and who were confirmed cases of SAM were included in the study. A detailed demography and data regarding anemia and related variables hemoglobin, mean corpuscular volume, peripheral smear, serum ferritin, Vitamin B12, and folic acid levels, were recorded and analyzed. The data were entered into MS-Excel sheet and analysis was performed using SPSS version 21.0. Results: About 95% of anemia prevalence was found among children with SAM and most cases were of nutritional anemia (81.79%). About 54.33% of the children had mild anemia, with 79.75% had iron deficiency as the most common cause, followed by Vitamin B12 and folic acid deficiency. Conclusion: The high prevalence of anemia suggests that it may contribute as a causal factor for hospitalization in severely malnourished children. We recommend future measures for prevention and control of anemia, including increased coverage of nutritional supplementation and fortification programs.